Neonatal outcomes in infants conceived using assisted reproductive technologies: A single medical center cohort study - Yen-Jhih Liao; Nai-Wen Fang; Cai-Sin Yao; Jenn-Tzong Chang; Hsiao-Ping Wang (Pediatrics and Neonatology)
Background: A significant rise in the use of assisted reproductive technology (ART) has been observed, but concerns about its impact on neonatal outcomes have been considered. The aim of this retrospective cohort study is to determine the association between ART and the risk of neonatal complications and congenital anomalies within a recent time period. Methods: This retrospective study enrolled infants born after 20 weeks of gestation at a tertiary hospital in Taiwan between January 2019 and December 2021. The study population was divided into two groups: (1) ART pregnancy group and (2) natural pregnancy group. Maternal and neonatal characteristics, pregnancy complications, and neonatal outcomes were compared between the two groups. Multivariate logistic regression was used to adjust for maternal characteristics, preexisting maternal conditions, pregnancy complications, delivery methods, and infant characteristics. Results: This study enrolled 1770 infants comprising 289 in the ART pregnancy group and 1481 in the natural pregnancy group. The ART pregnancy group showed higher rates of multiple births, preterm births, low birth weights, and longer hospitalization periods. In the stratified analyses that were conducted on singleton births, no significant difference was observed. In the case of multiple births, lower rates of preterm birth, low birth weight, and respiratory support were observed in the ART pregnancy group. After adjusting for maternal and infant characteristics, ART was not considered a significant risk factor for adverse neonatal outcomes, including mortality, complications, and congenital anomalies. Conclusion: Although ART pregnancies were more likely to result in multiple births and furthermore adverse outcomes, ART itself was not associated with an increased risk of poor neonatal outcomes. By implementing measures to control the number of implanted embryos, ensuring appropriate prenatal screening, and providing comprehensive postnatal care, the risks associated with increased multiple pregnancies caused by ART may be reduced.